Phase change of iron ore reduction process using EFB as reducing agent at 900-1200°C - Purwanto, Hadi; Mohd. Salleh, Hamzah; Rozhan, Alya Naili; Mohamad, A.S.; Zakiyuddin, Ahmad (Institute of Physics Publishing (IOP), 2018)
Treatment of low grade iron ore involved reduction of oxygen in iron oxide by using reductant such as carbon monoxide or hydrogen gas. Presently, carboneous materials such as coke/coal are widely used as a source to provide reducing gas, but some problem arises from this material as the gas can harm the environments. Therefore, empty fruit bunch biomass from oil palm becomes an alternative to replace the usage of coke/coal as their major composition is carbon and hydrogen. The idea of replacing coke with biomass will reduce the amount of carbon dioxide release as biomass is a carbon neutral and renewable source, and at the same time abundance of waste from oil palm industries can be overcome. Therefore, the aim of this research is to upgrade the low grade iron with reducibility more than 50% being used in iron and steel making. In this research, low grade iron ore are mixed together with EFB then is making into composite pellet before being reduced at certain parameter chosen. The variables involved in this research is composition EFB (10%, 30% and 50%), temperature (1000°C, 1100°C and 1200°C) and reduction time is fixed with 30 minutes. From the experiment conducted, the highest reducibility achieved is 76.37% at temperature 1200°C. While XRD analysis shows the existence of metallic iron phase started to form at 1000°C with composition of 30% of EFB. Meanwhile, from magnetization test show that at 1200°C the highest magnetic susceptibility is achieved as the dominance phase at 1200°C is metallic phase. Therefore it is an interesting alternative to replace coke with biomass for reducing agent in upgrading low grade iron into workable ores